Supernaturalist analytic existentialism: Critical notice of Clifford Williams’ Religion and the meaning of life - Metz, Thaddeus (International journal for philosophy of religion, 2021)
In this critical notice of Clifford Williams’ Religion and the meaning of life, I focus on his argumentation in favour of the moderate supernaturalist position that, while a meaningful life would be possible in a purely physical world, a much greater meaning would be possible only in a world with God and an eternal afterlife spent close to God. I begin by expounding and evaluating Williams’ views of the physical sources of meaning, providing reason to doubt both that he has captured all the central ones and that he has provided the right explanation of why we ought to care about them. Then I address Williams’ account of why God would greatly enhance the meaning of our lives, arguing that, if God could do so, then God could by the same token reduce their meaning as well, such that it is unclear that a world with God would offer a net gain in meaning. Finally, I take up Williams’ position that an eternal afterlife with God would greatly enhance the meaning of our lives, contending that, if it would do so, then it would to such an enormous degree as to make it hard to capture the intuition that a meaningful life would be possible in a purely physical world.